Standardisation of Nursery Technique of Tropical Pines III. Root Pruning of Pinus patula, Schiede & Deppe Seedlings in Nursery - a Study - Ghosh, R. C.; Singh, R. P.; Sharma, K. K. (Indian Forester, 1974)
no abstract